PENGARUH UMUR DAN PARITAS IBU YANG MENGALAMI PLASENTA PREVIA DI RUANG BERSALIN RSUD ULIN BANJARMASIN - nur cahyani; Rien Laily (Fakultas Kesehatan Masyarakat Universitas Dayanu Ikhsanuddin, 2022)
Until now, bleeding in obstetrics still plays an important role as the main cause of maternal death, one of obstetric bleeding is placenta previa which occurs around 7%. The causative factors include age and parity. Based on register data in the maternity ward of RSUD Ulin Banjarmasin for the last 4 years, 72 people (4%) in 2019, 65 people (3.8%) in 2020, 69 people (4.4%) in 2021 and 89 people (4.7%) in 2022. The purpose of this study was to determine the description of the age and parity of mothers with placenta previa in the delivery room at Ulin Hospital Banjarmasin. This study used a descriptive method, with a sample of all mothers giving birth. who experienced placenta previa from January to December were 89 people. The results of the study in the maternity ward of Ulin Hospital Banjarmasin, namely the most safe age (20-35 years) amounted to 70 people (78.7%) and the highest parity was safe parity (2 and 3) amounted to 51 people ( 57.3%). For pregnant women to have their pregnancy checked according to specified standards or in accordance with the recommendations of health workers so that they can detect the incidence of placenta previa early. pregnant.